2005
DOI: 10.2478/bf02475198
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative polymerization of acrylamide in the presence of thioglycolic acid

Abstract: Chemical polymerization of acrylamide at room temperature was examined by using thioglycolic acid-cerium (IV) sulfate and thioglycolic acid-KMnO 4 redox systems in acid aqueous medium. Water soluble polyacrylamides containing thioglycolic acid end groups were synthesized. The effects of the molar ratio of acrylamide to Ce(IV) n AAm /n Ce(IV ) , the polymerization time, the temperature, the monomer concentration, the molar ratio of cerium (IV) sulfate to thioglycolic acid and the concentration of sulfuric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…21,25,37,38 Because of low S H bonding energy, the formation of free radicals in reaction I in Scheme 1 is more likely than other reactions to initiate polymerization of AAm. It was reported that the formation of free radicals on carboxyl groups might be possible.…”
Section: Yield % =mentioning
confidence: 99%
“…21,25,37,38 Because of low S H bonding energy, the formation of free radicals in reaction I in Scheme 1 is more likely than other reactions to initiate polymerization of AAm. It was reported that the formation of free radicals on carboxyl groups might be possible.…”
Section: Yield % =mentioning
confidence: 99%
“…These parameters are: the molar ratios of acrylamide/ cerium(IV) sulfate (n AAm /n Ce(IV) = 100 and 200) at constant crosslinker and acid concentrations, the concentration of sulfuric acid (C H 2 SO 4 = 0.0125 and 0.025 mol/l) at the n AAm /n MBAA = 40 and the molar ratios of acrylamide to N,N′-methylene bis(acrylamide) for different acid and initiator concentrations. The radical generation in the redox reaction of meso-2,3-dimercaptosuccinic acid and cerium(IV) sulfate in acid-aqueous medium is supposed to occur by one electron transfer from meso-2,3-dimercaptosuccinic acid to Ce(IV) according to the reactions given in Figure 1 as reported in the literature [18][19][20][21][22]. Because of low S-H bonding energy, the formation of free radicals in reaction I in Figure 1 is more likely than other reactions to initiate crosslinking polymerization of acrylamide and N,N′methylene bis(acrylamide) and oxidative termination of polymer radicals is also possible by ceric ions [18,20,21].…”
Section: Preparation Of P(aam-mbaa) Hydrogelsmentioning
confidence: 99%
“…The radical generation in the redox reaction of meso-2,3-dimercaptosuccinic acid and cerium(IV) sulfate in acid-aqueous medium is supposed to occur by one electron transfer from meso-2,3-dimercaptosuccinic acid to Ce(IV) according to the reactions given in Figure 1 as reported in the literature [18][19][20][21][22]. Because of low S-H bonding energy, the formation of free radicals in reaction I in Figure 1 is more likely than other reactions to initiate crosslinking polymerization of acrylamide and N,N′methylene bis(acrylamide) and oxidative termination of polymer radicals is also possible by ceric ions [18,20,21]. In previous investigations, it is described that the formation of radicals on carboxyl groups may be possible [18][19][20][21][22].…”
Section: Preparation Of P(aam-mbaa) Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations